Failed in aging? Queering in living with dementia - Keller, Valerie (Frontiers in Sociology, 2023)
This article explores the ways in which living with dementia brings potentials to queer the concept of “successful aging” and associated notions of being human. Regarding the progressive development of dementia, it can be assumed that people affected, no matter how hard they try, will sooner or later fail to age successfully. They increasingly become a symbol of what is called the “fourth age” and are framed as an essentialized other. Against this backdrop, it will be examined to what extent the position in the outside enables people with dementia to abandon societal guiding ideals and undermine hegemonic-dominant notions of aging. Based on statements of people with dementia, it is shown how they develop life-affirming ways of being-in-the-world that run counter to the idea of the rational, autonomous, consistent, active, productive and healthy human being.